PENGARUH METODE EKSTRAKSI TERHADAP PEROLEHAN KEMBALI CANNABINOID DARI DAUN GANJA - Widnyani Astuti, Ketut (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2012)
A research on influence of extraction method to rendemen of cannabinoid coumpounds in cannabis leaves hadbeen conducted. The purpose of this research was to find an extraction method that could gain rendemen ofcannabinoid coumpounds. Cannabinoids of cannabis leaves was extracted by maceration and soxhletationmethod using petroleum eter as solvent. Concetrated extract was spotted HPTLC Si 60 GF 254. Plates wereeluted with hexane-diethyleter (80:20,v/v) in ascending twin chamber. Each peak was scanned on Camag TLCScanner III and identification of each insitu spectra were based on Rf and library spectra thus confirmed bycolour test with Fast Blue B salt. The results showed that maceration method gain a better rendemen thansoxhletation to identify the CBN, THC and CBD content in cannabis leaves. Ratio of CBN: (CBD+THC) frommaceration method were 1 : 21 meanwhile percetage ratio of THC to CBD were 1 : 266. CBD can not bedetected in soxhletation method.
Keywords: cannabinoides, Al-TLC, HPTLC, spectrophotodensitometry, extration.